Molecular Dynamics Approach on Dislocation Emission from Crack Tip Under Stepwise Loading in Aluminum - Andres Budiono; Hiroomi Homma (Journal of Applied Sciences and Advanced Technology, 2021)
Molecular dynamics (MD) simulation is carried out for pure aluminum under stepwise loading condition. This simulation aims to understand the experimental results on impact fracture toughness of aluminum alloys under short pulse loading.  The model used in this simulation is featured by  an atomistic model with single atom and the [111], [110], and [112] directions, a center-cracked plate model by the atomistic model with 17,402 number of atoms, and the periodic boundary condition in z-axis to postulate the plane strain condition. The obtained results are some dislocations emitted from crack tip, a void nucleation and growth taking place ahead of the crack tip. This micro void was initiated from a dislocation core when the load was kept being constant. This micro void never coalesced with the main crack as the distance between the micro void and the main crack was too far atomically and the micro void growth was stabilized. Energy balance investigation shows kinetic energy of the system was very small and almost constant during the process.   The potential energy increased as the external load increased and then became constant when the load became constant. Significant fluctuation of energy was observed during dislocation emission. Some amount of barrier energy must be released for the dislocation emission. The qualitative understanding can be provided by this molecular dynamic simulation.